"My Birth Control Makes Me Emotionally Psycho": Online Female Narratives about Contraceptives. Issue 2 (3rd April 2021) - Sitto, Karabo; Lubinga, Elizabeth
Abstract: Digital communication tools have become increasingly pivotal to facilitating the engagement and management of difficult health-related conversations. Peer conversations about individual women's experiences relating to the side effects of contraceptive use are not often held outside of medical contexts. To provoke conversations about birth control, on 9 January 2018, the Sexual and Reproductive Justice Coalition (SRJC) tweeted the results of a study about the severe side effects of using Depo-Provera (a contraceptive injection), triggering diverse discussions. This article reports on a study that analysed online narratives of tweets based on female experiences of effects suffered from contraceptive use and adopted a qualitative netnography design. Three theoretical perspectives, namely, the spiral of silence theory, the critical modernism theory, and the patient-centred model of health care, were relevant to the study. The results provided oft-unheard narratives of South African female voices on personal experiences and agency about contraceptive use. Within health communication, policymakers, as well as campaign designers, need to have a holistic understanding of the factors which may influence women's decisions to (dis)continue a contraceptive method. Such information is critical to designing interventions and programmes which will enable the achievement of important birth control goals and inform the design of effective policies or health campaign messaging. Online patient empowerment on various social media platforms needs to be monitored to avoid misinformation.